Development of local area network (LAN) at SMK 1 belitang madang raya - sunja ayu tiara sunja; Meilyana Winda Perdana (International Journal Cister, 2022)
The Internet is a global network of world computers, large and very broad where every computer is connected to each other from country to country around the world and contains various kinds of information [1]. The internet itself comes from the word interconnection networking which means the connection of many computer networks of various types and types, using communication types such as telephone, satellite, and others. In managing computer network integration using TCP or IP protocols. Local Area Network (LAN) consists of several computers connected in a network. In this network, each computer can access data from other computers. computers that are connected in a LAN can run hardware such as other computer printers, send data to other computer owners or play games together. The number of computers connected to the LAN is relatively small, such as home computers, internet cafes, schools and several other computers that are in one building. In this study, the researcher used a quantitative method approach to analyze the use of information and communication technology in the construction of a LAN network in the SMK Negeri 1 BMR school.